Soft Skills and Interpersonal Ability of CEOs for Company Existence in the Post-Covid-19 Pandemic Era - Hasyim, Nur; Nurjanah, Darul (KnE Social Sciences, 2024)
The post-Covid-19 pandemic period is uncertain because the pandemic hampers the running of business processes in almost all sectors due to the decline in market demand, production, and profits that occur in the company, so the CEO must optimize soft skills, interpersonal skills, and hard skills to survive in the company. This study aims to find out the soft skills and interpersonal skills that CEOs guide to exist in the post-Covid-19 pandemic period. This qualitative research investigates the CEO’s soft skills and interpersonal abilities for company existence in the post-Covid-19 pandemic era. Data were collected by interviewing the CEOs of PT Andal Software and PT Ikapunija Silver Expert, conducting documentation studies, and searching on trusted internet websites. Next, the data were analyzed qualitatively: data reduction, presentation, and conclusion. The results of the study were soft skills guided by CEOs to exist in the post-pandemic period, such as leadership, strategic management system, effective communication, technical skills, good culture, and faith. Meanwhile, interpersonal skills developed include utilizing words such as please, sorry, ladies and gentlemen, as well as optimizing questions and discussions with employees and consumers. Keywords: soft skill, interpersonal skill, company, post-Covid-19 pandemic